Reconstruction of the Fig 4E panel III. - Romuald Haase (22339777) (2025)
The conoid is a dynamic, tubulin-based structure conserved across the Apicomplexa that undergoes extrusion during egress, gliding motility, and invasion in Toxoplasma gondii. This organelle traverses the apical polar ring (APR) in response to calcium waves and plays a critical role in controlling parasite motility. While the actomyosin-dependent extrusion of the conoid is beginning to be elucidated, the mechanism by which it remains apically anchored to the APR is still unclear. RNG2, a protein localized to both the conoid and the APR, has emerged as a strong candidate for mediating this connection. Biochemical analysis revealed that RNG2 is an unstable protein, undergoing extensive proteolytic cleavage both in the parasite and in heterologous expression systems. Its biochemical properties, with the presence of large coiled-coil domains, likely facilitate the formation of concatenated assemblies, enabling RNG2 to serve as a dynamic and resilient bridge between the conoid and the APR. Using a combination of iterative ultrastructure expansion microscopy and immunoelectron microscopy, we confirmed the localization of RNG2 to the 22 tethering elements bridging the APR and the conoid. Conditional depletion of RNG2 led to the striking detachment of the intact conoid organelle from the APR, supporting an essential role for RNG2 as a tether. Cryo-electron tomography of conoid-less parasites revealed that, in the absence of RNG2, the apical vesicle remains anchored to the plasma membrane, while the rhoptries follow the detached conoid. Although RNG2 depletion only mildly reduces microneme secretion, the parasites are immotile and exhibit impaired rhoptry discharge, highlighting the critical role of proper conoid anchorage in motility and host cell invasion. Comprehensive mutagenesis of RNG2 identified distinct regions responsible for binding to the conoid and the APR, and demonstrated that the full-length, intact protein is essential for bridging these two structures and for its functional activity. Altogether, RNG2 emerges as a pivotal protein that ensures conoid functionality and coordination in Coccidia.